The Effect of Health Education Using Menshyc Media on Menstrual Hygiene Knowledge Among Elementary School Girls in Cisaga, Ciamis Regency - Herlanggie, Shevia Nur’aini; Kurniati, Citra Hadi (Proceedings Series on Health & Medical Sciences, 2025)
Low levels of menstrual hygiene knowledge are commonly found among adolescent girls due to a lack of information and health education. According to Basic Health Research (Riskesdas, 2016), out of 69.4 million adolescents in Indonesia, 63 million exhibit poor personal hygiene practices, particularly in maintaining reproductive health during menstruation. This study aims to analyze the difference in menstrual hygiene knowledge among female students before and after receiving health education using the Menshyc media. This research employed a quantitative approach with a pre-experimental design (one-group pretest-posttest without a control group). The study population consisted of 115 fifth- and sixth-grade female students from public elementary schools in the Cisaga region. A total of 82 respondents were selected using proportionate stratified random sampling. Data were collected through a structured questionnaire and analyzed using the Wilcoxon signed-rank test. Statistical analysis using the Wilcoxon test showed a significant difference in knowledge levels before and after the intervention, with a p-value of 0.001 (p 0.05). There is a statistically significant difference in menstrual hygiene knowledge among fifth-and sixth-grade female students before and after receiving health education using the Menshyc media at public elementary schools in the Cisaga region, Ciamis Regency.